DESIGN AND IMPLEMENTATION: ADAPTIVE LEARNING MANAGEMENT SYSTEM (LMS) WITH PEER ASSESSMENT FEATURES IN MICROTEACHING COURSES: DESAIN DAN IMPLEMENTASI: LEARNING MANAGEMENT SYSTEM (LMS) ADAPTIF DENGAN FITUR PENILAIAN REKAN SEJAWAT PADA MATA KULIAH MICROTEACHING - IMRO'ATUL HUSNA AFRIANI; St. Shabibatul Rohmah; Dian Arief Pradana (SOSIOEDUKASI, 2025)
Developing the teaching competence of pre-service teachers requires feedback that is effective, timely, and continuous. Microteaching is a required course where student teachers design and practice lessons, although it often faces problems because feedback from lecturers is limited by time and resources. To solve this, the study created an adaptive Learning Management System (LMS) with peer-assessment features. This research used the ADDIE model, which included assessing needs, designing the system, creating prototypes, implementing the model, and evaluating the results. The results show that the adaptive LMS had a positive impact on student learning. Based on feasibility criteria, most students rated the system “Valid,” with an average score of 80.8%. Peer feedback, collaboration, and reflection were the main strengths, while active participation still needed small improvements. Students found the LMS easy to use, though some had difficulties at first with the instructions. Overall, the system was practical, effective, and ready to use, with only minor changes required. This study demonstrates that an adaptive LMS with peer-assessment can enhance feedback, support reflection, and strengthen teaching skills in microteaching courses.